Pengaruh Tiga Macam Tingkat Protein Ransum (23, 20, dan 18%) terhadap Penampilan Ayam Broiler - Panca Dewi; Juju Wahju; Dawan Sugandi (Buletin Ilmu Makanan Ternak, 1990)
The aim of the experiment was to study the effects of protein levels in the diets on body weight gain, final body weight, feed consumption, feed conversion and to determine the income over feed and chick cost of the chickens. The experiment used 180 day old broiler chicks and it was conducted at the Department of Animal Production, Faculty of Animal Husbandry, Bogor Agricultural University (started November 2, 1984 until December 27, 1984). Analyses of variance were conducted for completely randomize design with 3 treatments and 6 replications. Significant differences in body weight gain, final body weight, feed consumption and feed conversion between diet of 23% protein and of 18% protein were apparent. The diet of 23% protein had the highest income over feed and chick cost.